The contribution of itch and skin severity improvements to the Dermatology Life Quality Index in patients with atopic dermatitis in baricitinib phase III trials. (1st June 2022) - Yosipovitch, Gil; Papp, Kim; Forman, Seth; Han, George; Waibel, Jill; Rueda, Maria J.; Sun, Luna; Chen, Yun‐Fei; Goldblum, Orin; Pierce, Evangeline; Silverberg, Jonathan I.
Abstract: With data from three monotherapy baricitinib phase III randomized clinical trials (RCTs), we conducted a posthoc mediator analysis to assess whether changes in itch or skin severity mediated the treatment effect over placebo on changes in health‐related quality of life. In this analysis, baricitinib demonstrated significant improvement in the Dermatology Life Quality Index for which itch mediated approximately half of the changes at weeks 4 and 16.